2014
DOI: 10.1016/j.bodyim.2014.07.010
|View full text |Cite
|
Sign up to set email alerts
|

“Appearance potent”? A content analysis of UK gay and straight men's magazines

Abstract: With little actual appraisal, a more 'appearance potent' (i.e., a reverence for appearance ideals) subculture has been used to explain gay men's greater body dissatisfaction in comparison to straight men's. This study sought to assess the respective appearance potency of each subculture by a content analysis of 32 issues of the most read gay (Attitude, Gay Times) and straight men's magazines (Men's Health, FHM) in the UK. Images of men and women were coded for their physical characteristics, objectification an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 37 publications
(78 reference statements)
3
42
0
Order By: Relevance
“…Nonetheless, that sex life satisfaction played some role in gay men's wellbeing is consistent with past studies (Biss & Horne, 2005;Martins et al, 2007). This is not surprising, not only because the gay male community is highly "sexualized" in media representations (Jankowski, Fawkner et al, 2014), but also because gay men are typically more sexually active than other groups (Biss & Horne, 2005;Gil, 2007). It warrants mentioning, however, that sex life satisfaction is associated with better wellbeing among heterosexual men and women as well (Smith et al, 2011), so this finding is not limited to gay men.…”
Section: Life Domain Satisfaction and Importancesupporting
confidence: 87%
See 2 more Smart Citations
“…Nonetheless, that sex life satisfaction played some role in gay men's wellbeing is consistent with past studies (Biss & Horne, 2005;Martins et al, 2007). This is not surprising, not only because the gay male community is highly "sexualized" in media representations (Jankowski, Fawkner et al, 2014), but also because gay men are typically more sexually active than other groups (Biss & Horne, 2005;Gil, 2007). It warrants mentioning, however, that sex life satisfaction is associated with better wellbeing among heterosexual men and women as well (Smith et al, 2011), so this finding is not limited to gay men.…”
Section: Life Domain Satisfaction and Importancesupporting
confidence: 87%
“…For instance, McArdle and Hill (2009) postulated that gay media presentation of the ideal male body type has a strong effect on gay male body image, as it promotes a certain body standard that is supposedly desirable but very difficult for most men to attain. This is consistent with recent research reporting more "appearance potent" content (i.e., more idealized, sexualized, and nude pictures) in gay men's magazines compared with heterosexual men's magazines in the UK (Jankowski, Fawkner et al, 2014). Jankowski, Diedrichs et al (2014) also found that gay men report more appearance-oriented conversations than heterosexual men do, and that this mediates the association between sexuality and body dissatisfaction.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is possible then, that the differences found in the UK sample are instead related to other factors that may differentiate British men from men in the other three countries (Swami et al, 2013). UK depictions of masculinity may be less clearly related to the internalization of body ideals (Jankowski, Fawkner, Slater, & Tiggemann, 2014). It has previously been reported that, among British males, the embodiment of masculinity was associated with resistance to conformity and the rejection of vanity or conscious and discernible efforts to improve physical appearance (Gill, Henwood, & McLean, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…These differences can be related to the fact that gays are particularly vulnerable to dissatisfaction with their bodies (Jankowski, Diedrichs, & Halliwell, 2014). Jankowski, Fawkner, Slater, and Tiggemann (2014) verified that the magazines aimed at gay men have more "appearance potent" male photos than the magazines aimed at heterosexual men by presenting more images of men with an ideal appearance.…”
Section: Discussionmentioning
confidence: 99%